DUTCH (Dried Urine Test for Comprehensive Hormones) In Preventing Diseases Related Hormonal Function - Asti Widuri; Rizka Fakhriani; Qorry Agustin; Astika Cahyarani (Universitas Muhammadiyah Surabaya, 2022)
Hormones released and absorbed by the human body in a balanced state will help create balance and health, while changes in hormone levels can cause various severe and chronic health problems. Hormone test is a method of measuring hormone levels in the body that can be used to diagnose and treat diseases, monitor patient health as a whole, or prevent the growth of certain health problems. This research might be the information about. the functional hormone test (DUTCH). This study presented a case of a 47 years old woman with history of chronic dysmenorrhea. The functional hormone testing was carried out on days 19-22 of the menstrual cycle in women with a regular period of 28 days. The result of DUTCH test in this patient were dominant 2-OH that she safe from the symptoms of estrogen dominance and low production of 4-OH, the methylation process was fluent so that the risk of cancer-related to estrogen dominance syndrome was low. Hormone examination through urine is intended to see metabolites (metabolic waste) hormones released through urine. By witnessing the estrogen & progesterone metabolites, it can be seen how much risk a person has Estrogen Dominance Syndrome.